2017
DOI: 10.14431/aw.2017.12.33.4.55
|View full text |Cite
|
Sign up to set email alerts
|

Is Board Gender Diversity a Driver of CEO Compensation? : Examining the Leadership Style of Institutional Women Directors

Abstract: In this investigation, we aim at examining the influence of institutional female directors on CEO compensation. Concretely, we investigate the impact of institutional female directors as a whole, differentiating also whether institutional female directors have business ties with the firm where they sit on boards (pressure-sensitive female directors) and do not have business links (pressure-resistant female directors). We hypothesize that there is a nonlinear association, concretely quadratic, between instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
(41 reference statements)
2
14
0
Order By: Relevance
“…However, the greater inclusion of female directors may exacerbate difficulties in achieving consensus, reducing team decision-making effectiveness and thus reducing performance [13]. The majority of previous studies have established a positive relationship between female directors and governance performance [29,37,41]. This study therefore hypothesizes: Hypothesis 2.…”
Section: Female Directors and Corporate Governancementioning
confidence: 91%
See 1 more Smart Citation
“…However, the greater inclusion of female directors may exacerbate difficulties in achieving consensus, reducing team decision-making effectiveness and thus reducing performance [13]. The majority of previous studies have established a positive relationship between female directors and governance performance [29,37,41]. This study therefore hypothesizes: Hypothesis 2.…”
Section: Female Directors and Corporate Governancementioning
confidence: 91%
“…Authors of References [3,29] believe that female directors are good supervisors, allowing them to compensate for shortcomings in external governance. Institutional female directors on boards play an important role in managerial monitoring and remuneration policies, thus affecting the corporate governance system [37]. The presence of female directors on boards also reduces the level of fraudulent financial reporting and enhances sustainability accounting practices [38,39].…”
Section: Female Directors and Corporate Governancementioning
confidence: 99%
“…Thus, García-Meca (2016) states that directors, being more cautious in remuneration policies, reduce the remuneration of the board members, given their ethical behavior, risk aversion and better ability to identify unethical conduct. Thus, the presence of the women on the Boards of Directors reduces opportunistic behaviors, leading to greater control of the salaries of the members of these boards (Pucheta-Martínez et al 2017). However, some studies show a positive relationship between the presence of the female gender and the remuneration of the Boards' members.…”
Section: Onementioning
confidence: 99%
“…With regard to PC, recent literature (e.g., Abdul et al 2018;Ding et al 2015;Fralich and Fan 2018;Fung and Pecha 2019;García-Meca 2016;Wu et al 2018) has shown that the effects of PC on the remuneration of board members and/or CEO are positive, negative or simply non-existent. In what concerns the effect of GD, while some studies in the literature have suggested that the latter increases the remuneration of Boards of Directors' members (e.g., Abdul et al 2018;O'Reilly and Main 2010), other studies either point to the contrary conclusion (e.g., Westphal and Zajac 1995), simply suggest that the effect, if any, is not significant (Fralich and Fan 2018;Fung and Pecha 2019;García-Meca 2016;Wu et al 2018) or detect a non-linear relationship (e.g., Owen and Temesvary 2019;Pucheta-Martínez et al 2017). It should be noted that studies devoted to the banking sector are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation